Very light asymmetric dark matter - Alonso Álvarez, Gonzalo; Gehrlein, Julia; Jaeckel, Joerg; Schenk, Sebastian (Journal of cosmology and astroparticle physics, 2019)
Very light dark matter is usually taken to consist of uncharged bosons such as axion-like particles or dark photons. Here, we consider the prospect of very light, possibly even sub-eV dark matter carrying a net charge that is (approximately) conserved. By making use of the Affleck-Dine mechanism for its production, we show that a sizable fraction of the energy density can be stored in the asymmetric component. We furthermore argue that there exist regions of parameter space where the energy density contained in symmetric particle-antiparticle pairs without net charge can to some degree be depleted by considering couplings to additional fields. Finally, we make an initial foray into the phenomenology of this scenario by considering the possibility that dark matter is coupled to the visible sector via the Higgs portal.
Gesehen am 15.12.2020